If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + -2(m + 7) = 2m + 14 Reorder the terms: 3m + -2(7 + m) = 2m + 14 3m + (7 * -2 + m * -2) = 2m + 14 3m + (-14 + -2m) = 2m + 14 Reorder the terms: -14 + 3m + -2m = 2m + 14 Combine like terms: 3m + -2m = 1m -14 + 1m = 2m + 14 Reorder the terms: -14 + 1m = 14 + 2m Solving -14 + 1m = 14 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. -14 + 1m + -2m = 14 + 2m + -2m Combine like terms: 1m + -2m = -1m -14 + -1m = 14 + 2m + -2m Combine like terms: 2m + -2m = 0 -14 + -1m = 14 + 0 -14 + -1m = 14 Add '14' to each side of the equation. -14 + 14 + -1m = 14 + 14 Combine like terms: -14 + 14 = 0 0 + -1m = 14 + 14 -1m = 14 + 14 Combine like terms: 14 + 14 = 28 -1m = 28 Divide each side by '-1'. m = -28 Simplifying m = -28
| x*2-7=10 | | 3m-2(m+7)=m+14 | | 8x*(13+10)=x | | (9m^3-6m^2+m-2)+(9m^3+6m^2-4m-2)= | | 20x+x*x*x-9x*x=0 | | (5x+6)+(-6x+5)= | | 20x+x*x*x+9x*x=0 | | 32x+7=15 | | 7+x+(4x+7)= | | 2x+4=16-x | | 4w=-1 | | 5x=6y | | 2x+3=147 | | 9x^4+4x^2+1=0 | | 10x^2-4X+12=Y | | 34-5x=4x+24 | | x^2-4x=2 | | x^2-605x+1206=0 | | 8-7x=98-42x | | 2x+3-4=3x+6+6 | | x^10*e^6= | | -9x^3+18x^2-12x-8= | | 2*x*x-8=42 | | 2*x=40 | | 21=v(v-4) | | 2xx-8=40 | | 3x^2+7x+13=11 | | 2x-3=64 | | y-.8y=74 | | -5+12=17x-3-16x | | -5x*-3+8= | | 7x+1=-20 |